Trocando Olhares: o desejo, o amor, a angústia e a dor na poesia de Florbela Espanca - Nascimento, Michelle Vasconcelos Oliveira do (2005)
In this work, Florbela Espanca poetry is analyzed. The objective is to prove that the loving thematic in her poetry tissues a connection among wish, love and sorrow. The psychoanalitic boarding is the basis to elucidate this connection,which begans with the sight, since mythology, passing by the portuguese literature begining periods and repeating itself in Florbela contemporanian poets. If Florbela poetry corroborates the portuguese literature tradiction, otherwise, it exposes the subject human being face, being a wishful creature